PEMBERDAYAAN IBU-IBU DASA WISMA MELALUI DAPUR SEHAT ATASI STUNTING (DASHAT) - ,; ,; , (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting is the condition of toddlers who have a height or body length lower than their age standard, indicating a lack of nutritional intake and poor environmental health. Based on WHO data in 2020, the global prevalence of stunting reached 22.2%, with Indonesia included in the Southeast Asia region which had a prevalence of 36.4%. In East Kalimantan Province, the prevalence of stunting in 2023 was recorded at 22.9%, while in Kutai Kartanegara Regency it reached 17.6%. In an effort to overcome this problem, BKKBN launched the DASHAT (Healthy Kitchens to Overcome Stunting) program which aims to provide balanced nutrition for families at risk of stunting through the use of local resources. This program involves community empowerment through a series of educational and training activities regarding nutrition and making nutritious food from local ingredients such as Moringa leaves. The results of this activity show an increase in community awareness and skills in preventing stunting, by implementing solutions to process local resources into healthy food.